Evolution Of Enterprise Property Contract Mechanism And Choice Of Governance Model Of SOEs - Cao, Pei (2008)
Enterprise theory is the area where in the past two or three decades wins the rapidest and most developments. It intersected with game theory, information economics and incentive mechanism, which largely enriches the content of microeconomics, and the same time helped people to have a better understanding of market mechanism and enterprise organization operation.